2003
DOI: 10.1046/j.1365-294x.2003.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Parentage assignment detects frequent and large‐scale dispersal in water voles

Abstract: Estimating the rate and scale of dispersal is essential for predicting the dynamics of fragmented populations, yet empirical estimates are typically imprecise and often negatively biased. We maximized detection of dispersal events between small, subdivided populations of water voles (Arvicola terrestris) using a novel method that combined direct capture-mark-recapture with microsatellite genotyping to identify parents and offspring in different populations and hence infer dispersal. We validated the method usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 44 publications
(70 reference statements)
6
114
2
Order By: Relevance
“…Assessing dispersal is of obvious importance in disciplines such as conservation biology, in which informed management decisions based on an understanding of population structure and movement, or lack thereof, must be made to help preserve species threatened by small population sizes (e.g. [2]). At the opposite end of the spectrum are pest and invasive species whose large population sizes and dispersal ability can threaten both ecological and agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing dispersal is of obvious importance in disciplines such as conservation biology, in which informed management decisions based on an understanding of population structure and movement, or lack thereof, must be made to help preserve species threatened by small population sizes (e.g. [2]). At the opposite end of the spectrum are pest and invasive species whose large population sizes and dispersal ability can threaten both ecological and agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…The type of samples obtained from natural populations has great implications for the reconstruction of parentage in studies using a combination of polymorphic molecular markers (DNA microsatellites), parentage analysis methods based on maximum likelihood estimators, and exclusion of individuals as potential parents (Jones and Ardren 2003;Telfer et al 2003;Koch et al 2008). Although the joint combination of these methods greatly increases the correct parentage assignment, the risk of two types of errors remains: false parentage assignment and the nondetection of true parents, in our case mothers (e.g., Oddou-Muratorio et al 2003;Shurtliff et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies only parents assigned with a 95% probability were considered (e.g., Aars et al 2006;Dugdale et al 2007;Lane et al 2008). In our study system it was impossible to exclude the candidate mothers (CPs) assigned with a 80% confidence (see also Telfer et al 2003). Our choice of retaining these CPs was supported by the simulations of candidate offspring-'false', non-reproducing, CPs, that demonstrated that only in 1% of cases (n = 787 offspring-CP combinations) a false CP was assigned as the mother with an 80% confidence.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of dispersal can, to a large degree, be determined by the genetic diversity seen within populations and the differentiation between populations: If gene flow can be observed between two relatively isolated populations, conclusions can be drawn that long-distance seed (or pollen) dispersal is taking place, or that the populations share a common source (Nichols and Hewitt 1994;Cain, Milligan et al 2000;Muller-Landau, Levin et al 2003;Walker, Hulme et al 2003;Paetkau, Slade et al 2004). Genetic diversity can also provide clues as to how long populations have been established (the more diverse a population is, the older it is likely to be), as well as the relative ages of populations (more genetically diverse populations may be older than the less diverse ones) (Gautschi, Jacob et al 2003;Telfer, Piertney et al 2003). Because microsatellites do not code for any proteins, most are under no selective pressure and enjoy relatively high rates of mutation (around one mutation per fifty generations).…”
Section: After Establishment Of An Invasive Species: Genetic Dispersamentioning
confidence: 99%